An accurate diagnosis contributes to delayed institutionalization and mortality: The ABIDE Project. Issue 4 (1st February 2022) - van der Flier, Wiesje M; Van Maurik, Ingrid S.; Mank, Arenda; Bakker, Els D.; de Wilde, Arno; Bouwman, Femke H.; Stephens, Andrew W.; Van Berckel, Bart N.M.; Scheltens, Philip
Abstract: Background: Even though there is no curative treatment for Alzheimer's disease (AD) yet, an accurate diagnosis is essential, as it is a starting point to arrange proper care, which in turn may lead to beneficial health outcomes. Amyloid‐PET contributes to an accurate diagnosis and we hypothesize that this predisposes toward a more benign disease trajectory in terms of rate of institutionalization and mortality. Method: We included consecutive patients who had their baseline visit at the Alzheimer center Amsterdam between 2015 and 2016. During this period, we offered amyloid‐PET to all participants. Patient underwent amyloid‐PET as part of their diagnostic work‐up and were propensity score matched with patients without amyloid‐PET (i.e. no‐PET). Propensity score matching was performed with nearest neighbor 1‐to‐1 matching without replacement and based on baseline characteristics, resulting in two matched groups of n=444 patients each. The endpoints of the study were admission to a nursing home and mortality retrieved from statistics Netherlands. Result: Patients (matched cohort) had a mean age of 64±8, 40% (n=353) female, MMSE 25±4 and 43% (n=379) had dementia at baseline. Mean follow‐up duration was 3±1 for institutionalization and 4±1 for mortality. In the amyloid‐PET group, 10% (n=45) of patients were admitted to a nursing home, compared to 21% (n=92) of no‐PET patients. The amyloid‐PET group (HR=0.48 [0.33‐0.70]) had a lower risk of institutionalization compared to no‐PET patients, corresponding to a 1.5 year delay in institutionalization. Moreover, patients with amyloid‐PET had a lower mortality rate compared to matched no‐PET patients (11% (n=49) vs 18% (n=81); HR=0.51 [0.36‐0.73]), which corresponds with a 1.4 year longer survival. We found no differences between amyloid‐positive and amyloid negative patients). Conclusion: We demonstrated that a more accurate diagnosis, operationalized by means of adding amyloid‐PET to the diagnostic work‐up, positively influenced time to institutionalization and death in memory clinic patients, independent of syndrome diagnosis. This provides evidence for the notion that a well‐informed patient has better health outcomes.